Time-response modelling of an ice cream cone-shaped UWB antenna in the 5G spectrum for IoT applications - Yoga Tri Nugraha; Adam Pangestu; Mawardi Mawardi; Muhammad Irwanto; Muzammil Jusoh (Institute of Advanced Engineering and Science, 2026)
The development of wireless communication technology, especially fifth-generation (5G) networks, requires ultra-wideband (UWB) antennas capable of supporting high-speed data transmission, low latency, and massive connectivity for internet of things (IoT) applications. This research proposes an ice cream cone shaped UWB antenna design with a semicircular patch, a conical transition structure, and a feed path, designed to produce a nearly omnidirectional radiation pattern with high efficiency. The design is modeled using CST Studio Suite for frequency domain analysis and MATLAB for time response analysis with a modulated Gaussian pulse signal input. Simulation results show that the antenna is able to maintain the input waveform with little amplitude attenuation and phase shift and maintain two dominant spectrum peaks at ±6 GHz without significant distortion. Return loss (S11) measurements show a bandwidth of 4.40 GHz(3.80–8.20 GHz) with a minimum value of –28 dB, while the voltage standing wave ratio (VSWR) is close to 1, indicating optimal impedance matching and low power reflection. The group delay is stable, and the 2D radiation pattern shows nearly omnidirectional characteristics. This antenna is deemed suitable for portable 5G IoT devices, with recommendations for physical fabrication and field testing.